City bus electrification in South Korea: Public preference identified through contingent valuation experiment - Lim, Hea Jin; Park, Sun-Young; Yoo, Seung-Hoon (Pergamon Press Ltd., 2025)
To respond actively to issues of climate change and particulate matters, the South Korean authorities have established a plan to electrify all city buses by 2030. This article explores public preferences for city bus electrification in South Korea through the application of contingent valuation (CV). A CV questionnaire was presented to 1000 randomly chosen households along with visual aids to induce their willingness to pay (WTP) for city bus electrification. The payment vehicle and the survey method were selected as bimonthly household income tax and person-to-person interviewing, respectively. As a method of eliciting the WTP, the one-and-one-half-bound dichotomous choice technique was utilized. To analyze the WTP data with numerous zeros, the spike model was employed. The results revealed statistically significant findings. The mean household WTP was obtained as KRW 5195 (USD 4.0) every two months. Expanding this figure to encompass the entire national population results in an annual national total of KRW 680.6 billion (USD 524.7 million). The cost involved in the electrification amounts to KRW 625.0 billion (USD 481.9 million) every year. Therefore, the national WTP outweighs the cost. City bus electrification can be socially justifiable. Furthermore, some policy issues regarding the success of city bus electrification are discussed.